Polymyxins leading to nephrotoxicity - Lolla, Siddhartha; Uddin, Shaik Nayeem; Supriya, Chinta; Singh, Thakur Nikhil (International Journal of Basic & Clinical Pharmacology, 2023)
Drug resistance gram-negative bacteria are the most hazardous type of germ because they cause life-threatening illnesses. Polymyxins are cyclic lipodecapeptide antibiotics that are effective against gram-negative bacteria like Acinetobacter, Pseudomonas, and other Enterobacteriaceae (such Klebsiella, Escherichia coli, and Serratia). Polymyxins kill bacteria by rupturing the bacterial outer membrane (OM). The main side effect of this antibiotic class is the development of kidney damage. Transposable genetic elements, such as MCR genes, can encode bacterial resistance to polymyxins. Colistin's prodrug is colistimethate sodium (CMS). Polymyxin dosage should be modified based on renal function. Polymyxins have demonstrated excellent clinical results, which have aided in the development of a better dosage regimen. Monte Carlo simulations were used to determine the most effective polymyxin dosages. Polymyxin resurgence has resulted in the eradication of multidrug resistant gram negative bacteria.